Rancang Bangun Sistem Pakar Untuk Mendiagnosa Kerusakan Hardware Komputer dengan Metode Forward Chaining - Muhammad Alfareza; Hetty Rohayani; Kevin Kurniawansyah; Noneng Marthiawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The large number of computer users who do not have sufficient knowledge about the initial handling of hardware damage results in many computer users or an institution spending a lot of money just to repair damage that occurs to computer hardware. Therefore, this expert system application was created to assist computer users in making an initial diagnosis of a computer hardware damage experienced along with solutions to overcome the damage. The process of developing this expert system uses the knowledge method with data collection techniques used, namely interviews and observation. While the inference method used in the development of this expert system uses the forward chaining method. The application used in the development of this expert system uses the AppSheet application.